Tiny-ML based person identification in dynamic motion - Ahmed, Mirza Raiyan; Nokib, Shahed Pervez; Nafee, Shadman Ahmad; Khondaker, Jannatus Sakira (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.